PEREMPUAN PEKERJA KEBUN SAWIT DI DESA BUKIT AGUNG KECAMATAN KERINCI KANAN KABUPATEN SIAK - Samosir, Rebeca; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Bukit Agung Village, Kerinci Kanan District, Siak Regency with the problems that are (1) How is the contribution of women plantation workers to the family economy? (2) How the pattern of decision making in the household of the oil palm plantation worker? The purpose of this research is to know the contribution of women plantation workers to the family economy and to know the pattern of decision making in the household of oil palm plantation workers. This research is a quantitative research. The sampling technique used in this study is by using the census method, with the number of respondents 40 people. To collect data, researchers used questionnaires, interviews, and documentation. Data obtained from the results of this study were analyzed by using a descriptive quantitative method. The results showed that the contribution of the average income contribution given by female seeds cites of 43.20%, this shows the contribution of women seed quotations in the medium category. Time outpouring for public activities is still not maximized because the activity is aimed only for side jobs and female oil palm seed quoting still focuses on its role in the domestic realm. Decision making in the family at most is the decision-making based on husband and wife equivalent, this proves in decision making husband and wife work together in making decisions in the family.Keywords: women oil palm plantation workers, contribution, time outpouring, decision making